2022
DOI: 10.1002/efd2.52
|View full text |Cite
|
Sign up to set email alerts
|

Exotic god fruit, persimmon (Diospyros kaki): Pharmacological importance and human health aspects

Abstract: The persimmon fruit (Diospyros kaki) belonging to the family Ebenaceae, is a famous conventional Korean medicinal herb. Calyx of persimmon has been used to prepare herbal drinks in Korea, China, and Japan due to its various functional ingredients, including fructose, glucose, and triterpenoid. In addition, persimmon is generally used as traditional medicine in Korea for the treatment of asthma, chronic bronchitis, and cough. Various useful constituents have been isolated and characterized from Diospyros specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Persimmons contain various nutrients such as vitamins and minerals, antioxidants such as β-carotene, βcryptoxanthin, lutein, zeaxanthin and lycopene, as well as pro-vitamin A [7,8]. Persimmon fruit can function as a drug to prevent cancer and heart disease and even function as a drug to reduce high blood pressure [9,10]. Persimmons contain antiproliferative activity as anti-cancer [11].…”
Section: Downstream Prospect Of Persimmon Fruitmentioning
confidence: 99%
“…Persimmons contain various nutrients such as vitamins and minerals, antioxidants such as β-carotene, βcryptoxanthin, lutein, zeaxanthin and lycopene, as well as pro-vitamin A [7,8]. Persimmon fruit can function as a drug to prevent cancer and heart disease and even function as a drug to reduce high blood pressure [9,10]. Persimmons contain antiproliferative activity as anti-cancer [11].…”
Section: Downstream Prospect Of Persimmon Fruitmentioning
confidence: 99%
“…Moreover, rutin is widely recognized for its anti-cancer abilities [43]. Interestingly, a recent study reported that rutin was among the polyphenols that were not detected in persimmon [44], albeit suggesting that further investigation was recommended. However, in this study, it was revealed that rutin was the main polyphenol, with quantities reaching as high as 164.24 µg/g and no less than 90 µg/g (Table 2).…”
Section: Content Of Rutin and Other Polyphenols In The Extractsmentioning
confidence: 99%
“…Generally, the main polyphenols in these fruits are flavonols (quercetin and rutin), hydroxycinnamic acids (caffeic, p-coumaric, and ferulic acids), hydroxybenzoic acids (gallic, vanillic, and syringic acids) and proanthocyanidin (catechin) [7]. Due to the content of those compounds, persimmon fruits show interesting nutritional properties and antioxidant, anticancer, anti-ageing, and cytotoxic activities [8], provide a natural defence against free radicals [9,10], and have a cholesterol-lowering effect [11].…”
Section: Introductionmentioning
confidence: 99%